Cardiac birth defects in a twin infant born to a woman with chronic myeloid leukemia on dasatinib. (April 2019) - Hermel, David J; Chiu, Victor; Hermel, Melody H; Tulpule, Anil; Akhtari, Mojtaba
Preclinical animal studies have demonstrated an association between maternal use of tyrosine kinase inhibitors and embryofetal toxicity; yet, multiple clinical case series have reported normal pregnancy outcomes and healthy infants in women on these medications during the course of their pregnancy. We describe a case of a woman with chronic myeloid leukemia who had taken the second-generation tyrosine kinase inhibitor dasatinib during the first 12 weeks of her dichorionic diamniotic twin pregnancy and subsequently delivered two low-birth weight infants, one with severe cardiac malformations and the other without apparent birth abnormalities. To our knowledge, this is the first reported case of fetal cardiovascular defects in an infant born to a woman on dasatinib during a twin pregnancy and supports current recommendations to avoid this medication during pregnancy. We also review relevant preclinical and clinical studies of tyrosine kinase inhibitor use during pregnancy and explore alternative therapeutic options for patients with chronic myeloid leukemia during pregnancy to aid clinicians in the appropriate management of these patients so as to minimize both maternal and fetal risks.